Normalizacja i ocena zgodności a systemy zarządzania jakością - Rogala, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the main issues connected with standardization and conformity assessment. It demonstrates the examples of wrong formulation of data connected with quality management systems which are being noticed in economic practice. On this basis it shows recommendations for terminology describing quality management systems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 186-191